If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(y + -8) = 2y + -44 Reorder the terms: 9(-8 + y) = 2y + -44 (-8 * 9 + y * 9) = 2y + -44 (-72 + 9y) = 2y + -44 Reorder the terms: -72 + 9y = -44 + 2y Solving -72 + 9y = -44 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -72 + 9y + -2y = -44 + 2y + -2y Combine like terms: 9y + -2y = 7y -72 + 7y = -44 + 2y + -2y Combine like terms: 2y + -2y = 0 -72 + 7y = -44 + 0 -72 + 7y = -44 Add '72' to each side of the equation. -72 + 72 + 7y = -44 + 72 Combine like terms: -72 + 72 = 0 0 + 7y = -44 + 72 7y = -44 + 72 Combine like terms: -44 + 72 = 28 7y = 28 Divide each side by '7'. y = 4 Simplifying y = 4
| 4x-23.1=x | | 8(x-4.1)=2.4 | | (X)(x)(x+6)=432 | | 2.4t+6.89=-7.03 | | -.3x+3.4=9.3 | | 25+.45x=40+25x | | -.3+3.4=9.3 | | 2.4t+6.89=7.03 | | 6x-22=56+4x | | a=2.4c+6 | | 2b+1=b+7 | | y=240+5x | | 3p+21=-6 | | y+140=5x-100 | | 4y-9=43 | | 3y=x-20 | | 5w+3w+4x+5x+10+5=c | | -5x^2+15x+1.7=0 | | x^2+4y^2-2x-24y+21=0 | | 2x^2+20x=-10 | | 12x^7+6x^4-30x^2=0 | | 2(1-y)=8m | | 2X-X-7=-1 | | 7z-3=25 | | 5(2f+3)=6f-15 | | -2(3x-5)=22 | | y=.28-.6x+1.3x-2.9 | | x^2-15x+(56.25)=74.25 | | 8X-2X-5=3+12 | | 93+8=101+93 | | 9x^2+48x+45=0 | | -2(4m-3)=4m |